ANALYSIS OF PROJECT-BASED LEARNING (PBL) IN TEACHING WRITING SKILLS OF ISLAMIC TEXTS TO AFL UNDERGRADUATE LEARNERS - Zubair , Ahamed (Revista Conhecimento Online: Diversidade e Inclusão Social, 2024)
This research aimed to develop and assess the efficacy of Project-Based Learning (PBL) in teaching Islamic Texts of Translation-II Practical (Arabic-English) Project (Code: 20BAMP603) and imparting Islamic Texts writing skills at the Postgraduate and Research Department of Arabic Literature and Language, within The New College, affiliated with the University of Madras, Chennai, India. Conducted by Prof. K. M. A. Ahamed Zubair, Associate Professor of Arabic in Chennai, Tamil Nadu, India, this study followed a Research and Development (R&D) design outlined by Borg and Gall. Data collection employed interviews, observations, questionnaires, and tests, analyzed through descriptive qualitative data analysis and descriptive statistics. This study aims to evaluate the impact of the project-based learning model on the acquisition of Arabic writing skills of Islamic Texts by focusing on research objectives, design, population, methodologies, and data analysis. Researchers adopted the analysis approach through a thorough review of existing literature.